Cadaver as the first silent medical teacher: Exploring bioethical perceptions of department of anatomy - Surajit Kundu; Anil R Sherke; Richa Gurudiwan (Asian Journal of Medical Sciences, 2022)
Background: Department of Anatomy with its time honored and integral essence, human cadaveric dissection has been trying to serve the medical profession since the inception of medicine. Every human cadaver who goes under the knife of medical student during anatomical dissection deserves special treatment and utmost respect. But unfortunately, probably the hidden curriculum of bioethical sentiments of the body donor and the human cadaver have been noted to become extinct from medical profession, until recently with the introduction of the new competency based medical education in India. Aims and Objectives: The present study attempts to dig out the noble practices followed in various medical schools to ensure the human cadaver gets the rightful respect and dignity. Our literature review reflects the practice of students’ conduct and habits on the 1st day of dissection. We emphasize guidelines that may be sincerely recommended to medical schools to ensure respectful humanity and honor towards the human cadavers. Materials and Methods: The psycho-social attitudes of MBBS students has been attempted to learn by distributing questionnaire to the 2019 batch MBBS students (n=60) of Late Shri Lakhiram Agrawal Memorial Government Medical College Raigarh (CG) during the foundation course (first 1 month of 1st year curriculum) and on their first encounter with the cadaver. Results: About 95.4% and 57.5% of students showed positive and negative perceptions. The religious beliefs and emotional attachments with the cadaver were noted to be as 23.33% and 76.11%, respectively. The sentiments included cognitive, affective, moral, and behavioral. Conclusion: The article attempts to focus the noble endeavor of the Cadaver as the first silent medical teacher who wishes to enlighten the pure minds of medical students with knowledge and empathy to be shown towards the patients. Based on the emotional observations made from the medical students on their first encounter with the cadaver, the present study anastomoses science and humanity with care, compassion, and dignity.